Finite Element Model for 3-D Analysis of Composite Plates - M. Lefik (Engineering Transactions, 1995)
Homogenization theory is applied to the elastic analysis of plate composed of many layers parallel to the middle plane of the plate. The cross-section of each stratum has its own, complex structure. We analyse first the microstructure of the plate to define the local perturbation of a global mean behaviour, due to nonhomogeneity. We describe this perturbation using first order terms in the asymptotic expansion of displacements in the power series of the small parameter. We use this description in the derivation of a plate-type element for the analysis of plates with multiple, parallel layers. In the kinematics defining the global behaviour of the plate, additional degree of freedom is included. We quote the formula for the stiffness matrix of an equivalenet homogeneous plate element. The computational process is then illustrated by an example.